The Search For Iraq's Weapons of Mass Destruction - Pearson, Graham S. author. aut Link
XXXIV, 338 p.
Keywords: This authoritative account explores the facts that lie behind the Weapons of Mass Destruction programmes in Iraq. Graham Pearson shows how these programmes were gradually uncovered through the efforts of UN specialist exerts, then by UNSCOM and UNMOVIC and finally by the Iraq Survey Group. The book analyses why there was no stockpile of chemical or biological weapons to be found in Iraq. Finally, it examines the lessons for inspection, verification and non-proliferation in the chemical and biological weapons prohibition regimes.